PENGARUH PEYULUHAN KESEHATAN TERHADAP PERILAKU MAHASISWA TENTANG PENCEGAHAN PENYALAHGUNAAN NARKOTIKA DI UNIVERSITAS HALU OLEO - Muhammad Zulfikarrahim; Pranita Aritrina; Adius Kusnan (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Drug abuse does not only have an impact on the decline of human quality, but also the amount and quality of crime. Based on data in 2016 there are an estimated 275 million people worldwide or around 5.6% of the world's population in the age range 15-64 years who have abused drugs at least once. There before, we must increase efforts to prevent one of them from educating students through counseling in order to avoid drug purchases so that, this study aims to know the effect of health education on students' behavior regarding the prevention of narcotics abuse at halu oleo university. This study was a quasi-experimental study with a pre-test post-test group design, research sited at Halu Oleo University with the independent variable was health campaign and the dependent variable was behavior. The sample was 64 respondents and was taken used the total sampling technique and analysis of the data used was Wilcoxon Test. Based on the results of the study obtained by using the Wilcoxon hypothesis testing P-value of 0.003 (≤ 0.05) is obtained so, that Ho is rejected and Ha is accepted which means there is a change in behavior. Whereas the control group obtained a P-value of 0.102 (≥ 0.05) meaning that in this group there was no change in behavior. There is an influence of health education on student behavior about preventing narcotics abuse at Halu Oleo University.